Reviews of environmental contamination and toxicology. Volume 239 - Voogt, Pim de (Springer, 2017)
Reviews of Environmental Contamination and Toxicology attempts to provide concise, critical reviews of timely advances, philosophy and significant areas of accomplished or needed endeavor in the total field of xenobiotics, in any segment of the environment, as well as toxicological implications.- Resumé vydavatele
Includes index.
Keywords: ekotoxikologie; znečištění vod; vodní toxikologie; těžké kovy; sanační práce; environmental toxicology; water pollution; water toxicology; heavy metals; remediation; elektronické knihy; sborníky; electronic books; papers of several authors